A prospective cohort study assessing the reactogenicity of pertussis and influenza vaccines administered during pregnancy - Regan, Annette; Tracey, L.; Blyth, C.; Richmond, P.; Effler, P. (Elsevier, 2016)
BACKGROUND: Pertussis vaccination during pregnancy can prevent 91% of infant infections. In 2015, antenatal pertussis vaccination programs were introduced across Australia. METHODS: To monitor the safety of this program, pregnant women who received trivalent influenza vaccine (TIV) and/or diphtheria-tetanus-acellular pertussis vaccine (dTpa) were surveyed by text message seven days post-vaccination about possible adverse events following immunization (AEFI). Univariate logistic regression models were used to calculate the odds of reporting an AEFI following dTpa compared to TIV. Similar analyses were used to compare AEFI reported by women who received a previous dose of dTpa in 2011/2012 as part of a state-wide cocooning program. RESULTS: Of 5155 women, 4347 (84.3%) replied; 10.8% indicated they experienced an AEFI. There was no difference in the proportion of women who reported any reaction by vaccine; however, women who received dTpa were more likely to report a local reaction than women who received TIV (7.1% and 3.2%, respectively; OR: 2.29; 95% CI: 1.61-3.26). There was evidence suggesting local reactions were more common among women with a previous dose of dTpa (11.4%) compared to women with no previous dose (6.0%; OR: 2.00; 95% CI: 0.95-4.25); 11 (0.3%) women reported attending a hospital emergency department. Subsequent follow-up indicated symptoms resolved and mother and infant were healthy. There was no difference in the proportion of women attending hospital by vaccine (p > 0.05). DISCUSSION: Data on systemic and local reactions following receipt of TIV and dTpa during pregnancy support the safety of antenatal vaccination.